2012
DOI: 10.1113/jphysiol.2012.236869
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionarily conserved differences in pallial and thalamic short‐term synaptic plasticity in striatum

Abstract: Key points• Recent studies have shown that the striatum and the basal ganglia are to a remarkable degree conserved throughout the vertebrate phylum.• As the basic organization of the neural machinery for action selection is present in the lamprey, it is essential to understand how the striatum is activated.• In this study we characterize the pharmacology and synaptic dynamics from the lateral pallium (LPal; cortex) and thalamus (Th), the main excitatory input to the striatum.• We show that, as in mammals, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
27
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 56 publications
3
27
0
1
Order By: Relevance
“…These ascending projections are possibly involved in sensory-mediated respiratory control. Of note, like other neurophysiological features (Ericsson et al, , 2013Stephenson-Jones et al, 2011Grillner and Robertson, 2015), the general characteristics and the basic functional role of inhibitory mechanisms involved in rhythmic activities, such as respiration, appear to be highly conserved throughout evolution. New findings on the lamprey respiratory network may be useful to provide insights into the basic mechanisms of the central rhythm or pattern generators (Grillner, 2006) and hints for further investigations on this topic not only in the lamprey, but also in higher vertebrates, including mammals.…”
Section: Resultsmentioning
confidence: 99%
“…These ascending projections are possibly involved in sensory-mediated respiratory control. Of note, like other neurophysiological features (Ericsson et al, , 2013Stephenson-Jones et al, 2011Grillner and Robertson, 2015), the general characteristics and the basic functional role of inhibitory mechanisms involved in rhythmic activities, such as respiration, appear to be highly conserved throughout evolution. New findings on the lamprey respiratory network may be useful to provide insights into the basic mechanisms of the central rhythm or pattern generators (Grillner, 2006) and hints for further investigations on this topic not only in the lamprey, but also in higher vertebrates, including mammals.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the intrinsic organization of the basal ganglia, including all components of the so-called direct and indirect pathways, are present in lamprey and have been conserved throughout the vertebrate phylum as a common mechanism for action selection (Pombal et al, 1997a,b;Ménard and Grillner, 2008;Ericsson et al, 2011;Robertson et al, 2012). The results presented here show that the segregated expression of dopamine D 1 and D 2 receptors in the direct and indirect pathways is also present in the phylogenetically oldest vertebrates, suggesting that this organization also forms a crucial part of the blueprint for the basal ganglia.…”
Section: Resultsmentioning
confidence: 99%
“…The stimulation intensity was set to one to two times the threshold strength (typically 10-100 μA) to evoke PSPs. To investigate the short-term dynamics of synaptic transmission, a stimulus train of eight pulses at 10 Hz was used together with a recovery test pulse 1.5 s (to ensure membrane potential returns to rest) after the eighth pulse (32). PSPs often started on the decay phase of previous responses, and to extract correct amplitudes the synaptic decay was either fitted by an exponential curve and subtracted or manually subtracted.…”
Section: Methodsmentioning
confidence: 99%
“…To achieve this, we have developed a preparation in lamprey that maintains the eye and the midbrain intact in vitro, which has allowed us to perform whole-cell recordings from identified gaze-controlling cells in the optic tectum, while delivering natural and focal light stimuli within the visual field and monitoring and manipulating the synaptic responses. The retinotopic map in the lamprey tectum and the aligned motor map have been described in considerable detail (22,26), and the lamprey nervous system from forebrain to spinal cord is experimentally very accessible, well described, and also conserved throughout vertebrate evolution (30)(31)(32).…”
mentioning
confidence: 99%